Crack-healing ability and strength recovery of different hot-pressed TZ3Y20A–SiC ceramics by heat treatment in air. (15th February 2015) - Zhang, Xiu-Ping; Ouyang, Jia-Hu; Liu, Zhan-Guo; Wang, Yu-Jin; Wang, Ya-Ming; Zhou, Yu
Highlights: Crack healing behavior of TZ3Y20A–SiC ceramics by suitable heat treatment in air. Four kinds of influencing factors of crack healing are evaluated. A complete strength recovery of TZ3Y20A–SiC is attained by crack self-healing. Crack closure and rebonding of crack wall due to formation of SiO2 glassy phase. Abstract: Crack-healing ability and strength recovery of different ZrO2 (Y2 O3 )–Al2 O3 –SiC (TZ3Y20A–SiC) ceramics have been investigated by tailoring heat treatment temperature, heat treatment time, SiC content and crack size. Heat treatment in air enhances distinctly the flexural strength of TZ3Y20A–SiC ceramics. A complete crack-healing of TZ3Y20A–10 vol%SiC ceramic can be realized by optional heat treatments at 1073 K for 30 h, 1273 K for 10 h or 1373 K for 5 h, respectively. With increasing the content of nanosize SiC particles from 10 to 20 vol%, the crack-healing process of TZ3Y20A–SiC ceramics speeds up at identical temperature levels. The pre-existing cracks with a width up to 0.45 μm are healed completely under the optimum heat treatment conditions, and the flexural strengths of crack-healed TZ3Y20A–SiC ceramics are completely recovered to the value of smooth specimens. Crack closure and rebonding of crack wall due to the formation of SiO2 glassy phase by oxidation reaction between SiC and the oxidizing atmosphere are dominant healing mechanisms in TZ3Y20A–SiC ceramics.